Complementary, Integrative, and Nondrug Therapy Use for Pain Among US Military Veterans on Long-term Opioids. Issue 9 (September 2020) - Goldsmith, Elizabeth S.; MacLehose, Richard F.; Jensen, Agnes C.; Clothier, Barbara; Noorbaloochi, Siamak; Martinson, Brian C.; Donaldson, Melvin T.; Krebs, Erin E.
Abstract : Background: Long-term opioid therapy for chronic pain arose amid limited availability and awareness of other pain therapies. Although many complementary and integrative health (CIH) and nondrug therapies are effective for chronic pain, little is known about CIH/nondrug therapy use patterns among people prescribed opioid analgesics. Objective: The objective of this study was to estimate patterns and predictors of self-reported CIH/nondrug therapy use for chronic pain within a representative national sample of US military veterans prescribed long-term opioids for chronic pain. Research Design: National two-stage stratified random sample survey combined with electronic medical record data. Data were analyzed using logistic regressions and latent class analysis. Subjects: US military veterans in Veterans Affairs (VA) primary care who received ≥6 months of opioid analgesics. Measures: Self-reported use of each of 10 CIH/nondrug therapies to treat or cope with chronic pain in the past year: meditation/mindfulness, relaxation, psychotherapy, yoga, t'ai chi, aerobic exercise, stretching/strengthening, acupuncture, chiropractic, massage; Brief Pain Inventory-Interference (BPI-I) scale as a measure of pain-related function. Results: In total, 8891 (65%) of 13, 660 invitees completed the questionnaire. Eighty percent of veterans reported past-year use of at least 1 nondrug therapy for pain. Younger age and female sex were associated with the use of most nondrug therapies. Higher pain interference was associated with lower use of exercise/movement therapies. Nondrug therapy use patterns reflected functional categories (psychological/behavioral, exercise/movement, manual). Conclusions: Use of CIH/nondrug therapies for pain was common among patients receiving long-term opioids. Future analyses will examine nondrug therapy use in relation to pain and quality of life outcomes over time.